Dynamic boron-doping switched chitin-based single-atom Pt catalyst for chemo-selective hydrogenation - Yan Li; Lijun Lu; Xueyu Jiang; Dali Yang; Jeng-Lung Chen; Abhishek Dutta Chowdhury; Wu Li; Xianglin Pei; Aiwen Lei (Nature Communications)
Abstract Biomass valorization is a way to promote the ‘waste-to-wealth’ concept, which is a pre-requisite condition for a future sustainable lifestyle. The direct utilization of natural polymer for value-added materials should be prioritized. With this object, we demonstrate a facile and economical method to prepare chitin-derived supramolecular nanowires-stabilized single-atom sites Pt catalysts (SS-Pt-CSNs). A comprehensive characterization shows the structure of single-atom Pt coordinated with the organic supramolecular (ligand-type) entity, which is both flexible (like in homogenous catalyst) and robust (like in heterogenous catalyst). Such hybrid characteristics of these SS-Pt-CSNs materials exhibit excellent catalytic performance for chemo-selective hydrogenation of various unsaturated bonds with a selectivity of more than 90:1 and a high turnover number (TON) of 121,350. Mechanistic studies demonstrate that both empty coordination sites of Pt and dynamic B-doping are the key factors for exceptional efficiency and high selectivity.